Antifungal effect of calsium hydroxide and cresotin against candida albicans as root canal treatment materials - Aprilia, Aprilia; Cevanti, Twi Agnita; Soesilo, Diana; Damaiyanti, Dian Widya; Velisia, Jessica (Padjadjaran Journal of Dentistry, 2021)
Introduction: Candida albicans can cause quiet high prevalance of root canal treatment failure (35%). Candida albicans are difficult to eliminate and resistant to Calsium hydroxide. Therefore the research was conduct to determinate sterilization material which is effective as antifungal material to eliminate Candida albicans so can minimize the possibility of falure in root canal treatment. Purpose Obtain the optimum concentration of paste that consist of Calsium hydroxide powder combine with Cresatin liquid against the Candida albicans and must be safe to used in root canal tratement medication. Method: The initial examination of antifungal activities was carried out using the disc diffusion with spread plate technique. Medium that used in this method is Medium SGA (Saburoud’s Glucose Agar). Result: The result of the One-way ANOVA test showed a significant value of p= 0,000 (p<0,05). The result of Least Significant Difference test showed that each group had a significant difference because the value of p=0 (p<0,05).  There is significant difference between each group. Conclusion: The most effective as antifungal against Candida albicans is in mixing 1:2 of calsium hydroxide powder and Cresotin liquid which mean 1 full measuring spoon and 2 drops of Cresotin liquid. Mixture of Ca(OH)2 with metacresylacetate produce a chemical reaction namely calsium cresilate and Acetic acid. Calsium cresilate is strong disinfectant. Acetic Acid dissociates and releases hydroxyl ions (H+). Changes in pH cause the transformation of Candida albicans from Y form into M form so it inhibitis cell division.